Safety of low‐dose oral minoxidil treatment for hair loss. A systematic review and pooled‐analysis of individual patient data. Issue 6 (7th September 2020) - Jimenez‐Cauhe, Juan; Saceda‐Corralo, David; Rodrigues‐Barata, Rita; Moreno‐Arrones, Oscar M.; Ortega‐Quijano, Daniel; Fernandez‐Nieto, Diego; Jaen‐Olasolo, Pedro; Vaño‐Galvan, Sergio
Abstract: low dose oral minoxidil (OM) is an increasingly used treatment for androgenetic alopecia and other types of hair loss. to analyze available data of patients treated with OM, focusing on safety and adverse effects. a search in PubMed and EMBASE was performed for studies reporting the treatment of alopecia with OM. Individual patient data available for pooled‐analysis were sex, dose of OM, presence of hypertrichosis and lower limb edema. 14 studies including 442 patients were analyzed. OM was used at doses between 0.25 and 5 mg, for eight different types of alopecia. Hypertrichosis was observed in 24% of patients. All doses had an increased odds ratio of hypertrichosis, compared to 0.25 to 0.5 mg ( P  < .001). Pedal edema was observed in 2% and was also associated with higher doses of OM ( P = .009). Postural hypotension and heart rate alterations occurred only in 1.1% and 1.3% of the patients, respectively. Efficacy of OM could not be analyzed due to heterogeneous studies. However, four studies using OM for androgenetic alopecia reported a clinical response in 70% to 100% of the patients. Low dose OM is a safe and well‐tolerated treatment for hair loss, presenting a lower adverse effect rate than standard doses.